Special Measures for Quality and Challenged Providers: Study Protocol for Evaluating the Impact of Improvement Interventions in NHS Trusts - Naomi Fulop; Estela Capelas Barbosa; Melissa Hill; Jean Ledger; Christopher Sherlaw-Johnson; Jonathan Spencer; Cecilia Vindrola-Padros; Steve Morris (Kerman University of Medical Sciences, 2020)
Background Healthcare organisations in England rated as inadequate in terms of leadership and one other domain enter the Special Measures for Quality (SMQ) regime to receive increased support and oversight. There is also a 'watch list' of challenged National Health Service (NHS) providers at risk of going into SMQ that receive support. There is limited knowledge about whether the interventions used to deliver this support drive improvements in quality, their costs, and whether they strike the right balance between support and scrutiny. The study will seek to determine how provider organisations respond to these interventions, and whether and how these interventions impact organisations' capacity to achieve and sustain quality improvements over time.   Methods This is a multi-site, mixed methods study. We will carry out interviews at national level to understand the programme theory underpinning the interventions. We will conduct 8 NHS case studies to explore the impact and implementation of the interventions that form part of the SMQ and challenged providers programme. We will use a conceptual framework based on models of organisational readiness for change and draw on board maturity research for implementing quality improvement. We will also review the use of quantitative metrics and data for tracking the progress of improvements in quality of care and sustainability upon leaving SMQ, as well as the costs and benefits of the interventions through a cost-consequence analysis (CCA).   Discussion High-quality interventions that successfully support struggling healthcare organisations are essential and an issue that is an international concern. Our study will allow a greater understanding of the programme theory, impact, and staff views and experiences of the SMQ and challenged providers regime. Formative feedback will be reported to key stakeholders.